(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aims to evaluate the outcomes of digital transformation (DT) implementation at Military Hospital 7B during the 2017–2024 period, thereby establishing a foundation for formulating specific solutions to enhance the quality and efficiency of DT operations. Methods: The evaluation was conducted based on the criteria for information technology (IT) application stipulated by the Ministry of Health (Circular No. 54/2017/TT-BYT) and the Government’s Project 06/QĐ-TTg. Results: The Hospital achieved an overall Level 2 in IT application. Specifically, the Hospital Information System (HIS) reached Level 4, and IT Infrastructure reached Level 3. Key achievements include the successful deployment of HIS for the management of medical examination and treatment, the management of lifelong electronic medical records, the implementation of cashless payment systems, and successful data interoperability with the Social Security agency. However, the Hospital continues to encounter internal challenges, such as limited financial resources allocated for DT, heterogeneous infrastructure, and a lack of application of advanced digital technologies, including the Internet of Things (IoT), Artificial Intelligence (AI), Cloud Computing, and Big Data analytics. Conclusion: The status of digital transformation at Military Hospital 7B during the 2017–2024 period has been analyzed. Utilizing SWOT analysis and expert consultation, the study proposes leveraging core IT personnel and modern communication infrastructure (5G) to deploy telemedicine; standardizing the training of medical staff regarding IT planning to enhance precision in clinical practice and treatment; and investing in synchronous infrastructure to mitigate system risks.